Casual vacancy - Rowling, J. K. (Boston Signet Book, 2012)
This is a wonderful novel. JK Rowling's skills as a storyteller are on a par with RL Stevenson, Conan Doyle and PD James. Here, they are combined with her ability to create memorable and moving characters to produce a state-of-England novel driven by tenderness and fury
Keywords: Fiction